Strategi Pengembangan Usaha Tani Jahe di Desa Kunjorowesi - Aida Aida; Sri Karuniari Nuswardhani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This thesis examines the strategy for developing ginger farming in Kunjorowesi Village with the aim of increasing local agricultural income and sustainability. This research aims first, to identify factors that influence ginger farming income, and second, to evaluate the potential for developing ginger farming strategies that can increase income and agricultural sustainability. The research method uses observation techniques, interviews with farmers, and documentation to collect data. The analysis was carried out using the SWOT analysis model to identify strengths, weaknesses, opportunities and threats in ginger farming in Kunjorowesi Village The research results show that internal factors such as large areas of land, favorable land conditions, and the availability of skilled labor, as well as external factors such as supportive agro-climatic conditions and large market demand, have the potential to support the development of ginger farming businesses. However, there are also challenges such as limited capital, distance to farming locations, and interference from Plant Pest Organisms (OPT). Based on the SWOT analysis, a development strategy using the SO (Strengths-Opportunities) approach is recommended to utilize internal strengths and external opportunities. This strategy includes optimizing land use with skilled labor and strengthening cooperation between farmers, government and traders to improve marketing information.